Pengaruh Pengalaman Praktik Kerja Lapangan Terhadap Minat Berwirausaha Bidang Fashion - Adiella, Queeny Diesca; Mayasari, Peppy (Jurnal Riset Multidisiplin dan Inovasi Teknologi, 2025)
The purpose of this study is to 1) Describe the extent of the Field Work Practice experience of class XII Fashion Design students at SMK Negeri 1 Jabon. (2) Describe the extent of the interest in entrepreneurship in the fashion sector of class XII Fashion Design students at SMK Negeri 1 Jabon. (3) Analyze the influence of Field Work Practice experience on the interest in entrepreneurship in the fashion sector of class XII Fashion Design students at SMK Negeri 1 Jabon. This study is a type of quantitative research with an ex post facto approach that has been carried out at SMK Negeri 1 Jabon. The research sample was class XII Fashion Design students, obtained using convenience sampling techniques of 35 students. Data collection in this study used a closed questionnaire. In this study, descriptive analysis, prerequisite tests and hypothesis tests were carried out using a simple linear regression test with a sig.5% level. The results of the study showed that (1) Field work practice experience showed an average (mean) of 55.49 in the high category. (2) The interest in entrepreneurship in the fashion sector shows an average result (mean) of 57.43, which is included in the high category. (3) There is an influence between field work experience and interest in entrepreneurship with the equation Y = 36.709 + 0.373X. The coefficient of determination (R Square) shows 14%. So, the field work experience contributes 14% to the interest in entrepreneurship in the fashion sector of class XII Fashion Design students of SMK Negeri 1 Jabon, while the remaining 86% is influenced by other factors, namely environmental factors, family factors, economic factors.